Transformasi Manajerial Di Lembaga Pendidikan Anak Usia Dini Di Era Revolusi Industri 4.0 - Ninik Hidayati; Nurul Hakim; Aisyah Amatul Qayyum (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study aims to analyze managerial transformation in early childhood education institutions (PAUD) in the era of the Fourth Industrial Revolution, focusing on the role of technology, leadership, and digital managerial skills in enhancing early childhood education management. The findings indicate that the implementation of technology in PAUD management, such as the use of classroom management applications and communication platforms with parents, has had a positive impact on operational efficiency and education quality. However, the greatest challenge lies in the need for PAUD managers to develop digital managerial skills to optimize technology use. Leaders who are adaptive to technological changes and able to integrate them into management systems can strengthen PAUD management and improve educational quality. Therefore, continuous training for PAUD managers is essential to meet the demands of the digital era.